Meta-analysis of the clinicopathological significance of miRNA-145 in breast cancer. Issue 9 (18th September 2020) - Lv, Peng; Zhang, Zhenzhu; Hou, Li; Zhang, Yayue; Lu, Lingeng; Wang, Chong; Shi, Fengqin
Abstract: Low expression of tumor suppressor microRNA (miRNA) and high expression of carcinogenic miRNA promote the occurrence and progression of human cancer. Most studies show that miR-145 is a tumor suppressor miRNA, and is closely related to the clinicopathology of breast cancer. However, the results are still inconsistent. Therefore, we conducted a meta-analysis on the basis of eligible studies to summarize the possible correlation between miR-145 and the clinicopathology and prognosis of breast cancer. Using PubMed, Embase, Web of Science, Wanfang and CNKI, we searched all published papers written in either English or Chinese on miR-145 expression in breast cancer from 1990 to November 2019 for meta-analysis. We used standardized mean difference (SMD) to evaluate the differential expression of miR-145 in breast cancer tissues and adjacent normal tissues or normal breast tissues. We found that miR-145 expression was significantly lower in breast cancer tissues than that in adjacent normal tissues (SMD = −2.93, P <0.0001) and in healthy women (SMD = −0.52, P =0.009). miR-145 expression was lower in breast cancer patients with ER-positive (SMD = 0.65, P <0.001), HER-2-positive (SMD = −1.04, P <0.001), compared with their counterparts, respectively. In addition, breast cancer patients with low expression of miR-145 had larger tumor diameters (SMD = −1.97, P <0.001) and lymph node metastasis (SMD = −1.75, P <0.001) that are unfavorable prognostic factors. Conclusion: Low miR-145 is observed in breast cancer, which is closely related to molecular subtypes and unfavorable factors of breast cancer. These findings indicate that miR-145 is tumor suppressor miRNA, and may be a potential diagnostic and prognostic marker in breast cancer.